2013
DOI: 10.1021/ac4022117
|View full text |Cite
|
Sign up to set email alerts
|

Solid Contact Ion-Selective Electrodes with a Well-Controlled Co(II)/Co(III) Redox Buffer Layer

Abstract: Solid contact ion-selective electrodes (ISEs) typically have an intermediate layer between the ion-selective membrane and the underlying solid electron conductor that is designed to reduce the irreproducibility and instability of the measured electromotive force (emf). Nevertheless, the electrode-to-electrode reproducibility of the emf of current solid contact ISEs is widely considered to be unsatisfactory. To address this problem, we report here a new method of constructing this intermediate layer based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
76
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 52 publications
(69 reference statements)
5
76
0
1
Order By: Relevance
“…Measurements were accomplished in the concentration of pCu range 1.80-3.88 where a linear relationship was found between the EMF values of the electrode and pCu. This was in accordance with the Nernst equation [32] and allowed to determine the standard values of EMF (E°) and slope of response curve (s), used afterwards in Hyperquad 2008.…”
Section: Ise Titrationsmentioning
confidence: 99%
“…Measurements were accomplished in the concentration of pCu range 1.80-3.88 where a linear relationship was found between the EMF values of the electrode and pCu. This was in accordance with the Nernst equation [32] and allowed to determine the standard values of EMF (E°) and slope of response curve (s), used afterwards in Hyperquad 2008.…”
Section: Ise Titrationsmentioning
confidence: 99%
“…Conducting polymers,s uch as polypyrrole [8] or PEDOT, [9] offer ah igher redox capacity than carbon since the target ions can be inserted in the polymer upon reduction of the polymer backbone.N evertheless,c onducting polymers are characterized by aw ide range of redox potentials which renders the prediction and long-term stability of the standard potential difficult. [11,12] Nevertheless,t his approach requires the composition of the ISM to be altered. [10] Another approach is adding ah ydrophobic redox couple as a" redox buffer" into the ISM, resulting in quite remarkable initial reproducibility.…”
mentioning
confidence: 99%
“…Based on a similar principle, Buhlmann and subsequently Schuhmann showed that a metallic redox couple may also buffer the interfacial inner potential. 6 Different to the steady-state behavior in potentiometry, it was recently shown that reversible ion-transfer through an ionophore-based membrane can be established by oxidation/reduction of the CP situated underneath of the membrane (Scheme 1c, Fig S1). 7 Clearly, research in the field over many years has alluded to a CP transducing mechanism relying on the ionic buffer capacity mediated by a doping agent resulting in a high redox capacitance.…”
mentioning
confidence: 99%